2014
DOI: 10.1093/europace/euu192
|View full text |Cite
|
Sign up to set email alerts
|

Is the acetylcholine-regulated inwardly rectifying potassium current a viable antiarrhythmic target? Translational discrepancies of AZD2927 and A7071 in dogs and humans

Abstract: Based on the present series of experiments, an important role of IKACh in human atrial electrophysiology, as well as its potential as a viable target for effective management of AF, may be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
1
23
2
Order By: Relevance
“…It has been reported that NTC‐801 (50), a benzopyrene derivative, and AZD2927 (51), a benzamide‐related compound, can selectively inhibit I KACh at submicromolar concentrations. However, the drugs failed to revert paroxysmal AF and atrial flutter, respectively, in patients (50, 51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that NTC‐801 (50), a benzopyrene derivative, and AZD2927 (51), a benzamide‐related compound, can selectively inhibit I KACh at submicromolar concentrations. However, the drugs failed to revert paroxysmal AF and atrial flutter, respectively, in patients (50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NTC‐801 (50), a benzopyrene derivative, and AZD2927 (51), a benzamide‐related compound, can selectively inhibit I KACh at submicromolar concentrations. However, the drugs failed to revert paroxysmal AF and atrial flutter, respectively, in patients (50, 51). The results are not surprising, given the fact that I KACh is not constitutively active in patients with paroxysmal AF (52), let alone in atrial flutter whose mechanism differs from that of AF (53).…”
Section: Discussionmentioning
confidence: 99%
“…Besides a role of I K1 in AF, also constitutive I KACh activity has been associated with AF in humans and was subsequently suggested as a potential target in AF treatment . Indeed, I KACh inhibition in dogs with rapid atrial pacing induced AF results in prolongation of the effective refractory period and cardioversion to SR . Currently, there is no evidence that PA‐6 inhibits I KACh , but previous studies reported that I KACh action is reduced by some anesthetic agents .…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological block of I K,ACh in in vitro and ex vivo experiments showed promising antiarrhythmic effects. However, recent studies have found I K,ACh block to be ineffective both in increasing the left-atrial ERP in vivo ( Walfridsson et al, 2015 ) and reducing AF burden in clinical trials ( Podd et al, 2016 ). Pharmacological effects and pathways activated by acetylcholine that are currently not implemented in the existing computational models (e.g., crosstalk with CaMKII and β-adrenergic stimulation) might explain the disagreement between in vitro , in silico , and clinical studies.…”
Section: Computational Pharmacology In Afmentioning
confidence: 99%